ANALISIS GERAKAN LITERASI MELALUI MBOJO ITOE BOEKOE DALAM PENINGKATAN MINAT BACA DI KOTA BIMA - Muhammad Aditya Rachman; Andi Muhammad Aminullah (Yayasan Nusantara Hasana Berdikari, 2026)
This study discusses the analysis of literacy movements carried out by the Mbojo Itoe Boekoe (MIB) community in an effort to increase reading interest among the people of Bima City. The research focuses on: (1) the form of literacy movement carried out by MIB in the community of Bima City, (2) supporting and inhibiting factors in increasing reading interest through MIB, and (3) the views of literacy observers and the general public on the literacy movement carried out by MIB. This study uses a qualitative descriptive method with the aim of describing the research object in depth. The main data source comes from the founder of the MIB community, while data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and conclusion drawing. The results show that before implementing literacy activities, MIB first conducts surveys to prepare human resources and work programs, as well as to adjust to community needs so that literacy activities are positively received. In addition to having advantages such as collaboration with other communities and active participation in the Literacy Culture Camp, MIB also faces several obstacles that hinder its activities. The presence of MIB book stalls in public spaces helps the community and encourages the growth of critical thinking. This research is expected to serve as material for evaluating and strengthening the MIB literacy movement.